北极楚科奇海氟氯烃CFC-11的分布特征及其化学示踪 - 郑淑兰; 邓永智; 袁晓婕; 李文权 (2010)
2008年7—9月于北极楚科奇海采集了17个站位不同深度的海水水样,用吹扫捕集与气相色谱相结合的方法分析氟氯烃CfC11(CCl3f)的含量分布,并结合温度、盐度、溶解氧等水文和海洋化学数据用于楚科奇海水的化学示踪研究.结果表明,楚科奇海表层水中CfC-11的含量在2.95--8.81 PMOl/kg之间,表层水与30 M层水还没完全混合;HEr-Ald浅滩南边为夏季太平洋入流水,而以北仍然为冬季陆架残留水;CfC-11高值进一步证实阿纳德尔水、白令海陆架水与阿拉斯加沿岸流在bArrOW峡谷混合,CfC-11低值则证实北极中层水增暖现象,CfC-11表层含量的显著增加表明楚科奇海陆坡区离岸较近的地方受到河流径流的影响. Seawater samples were collected at 17 stations in the Chukchi Sea from July to September in 2008,and CCl3F(CFC-11) was measured with gas chromatography coupled with a purge-trap concentrator system.The datas of CFC-11 were used for seawater tracer study together with temperature,salinity and DO.The results showed that the concentrations of CFC-11 in surface water were 2.95 pmol/kg to 8.81 pmol/kg,and the shallower than 30 m water had not commingle entirety,and to the south of the Herald Shoal was summer Pacific Ocean water,but to the north was winter Chukchi Sea residual water.High amount of CFC-11 confirmed that the Anadyr water,Bering sea shelf water and Alaska coastal current were mixed in the Barrow Canyon,and low amount of CFC-11 approved the phenomenon of warming of middle water in north pole,the markely increase of CFC-11 in surface water meant that the less distant offshore stations had great influence by river stream. 国家自然科学基金(40276035)